2012
DOI: 10.1111/j.1365-2966.2011.20100.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the formation of inner bars: photometry, kinematics and stellar populations in NGC 357★

Abstract: Double‐barred galaxies are common in the local Universe, with approximately one‐third of barred spirals hosting a smaller, inner bar. Nested bars have been proposed as a mechanism to transport gas to the very central regions of the galaxy, trigger star formation and contribute to the growth of the bulge. To test this idea, we perform for the first time a detailed analysis of the photometry, kinematics and stellar populations of a double‐barred galaxy: NGC 357. We find that this galaxy is either hosting a pseud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 80 publications
9
40
1
Order By: Relevance
“…This is in agreement with the findings of Sánchez-Blázquez et al (2011) for four different barred galaxies, although their analysis methods were quite different. Old stellar populations have also been found within bars by some studies (Pérez, Sánchez-Blázquez, & Zurita 2007;Pérez, Sánchez-Blázquez, & Zurita 2009;de Lorenzo-Cáceres et al 2012;de Lorenzo-Cáceres, Falcón-Barroso, & Vazdekis 2013), in general agreement with our results, but note that in this case it is not clear how to relate these ages to the bar age (an old population could have been assembled into a bar morphology very recently).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the findings of Sánchez-Blázquez et al (2011) for four different barred galaxies, although their analysis methods were quite different. Old stellar populations have also been found within bars by some studies (Pérez, Sánchez-Blázquez, & Zurita 2007;Pérez, Sánchez-Blázquez, & Zurita 2009;de Lorenzo-Cáceres et al 2012;de Lorenzo-Cáceres, Falcón-Barroso, & Vazdekis 2013), in general agreement with our results, but note that in this case it is not clear how to relate these ages to the bar age (an old population could have been assembled into a bar morphology very recently).…”
Section: Discussionsupporting
confidence: 91%
“…We note that σ-hollows have been observed in other double-barred galaxies (de Lorenzo-Cáceres et al 2012Du et al 2016) and they seem, so far, an ubiquitous property of these systems. This result reinforces the validity of σ-hollows as kinematic diagnostics for identifying doublebarred galaxies.…”
Section: Stellar Kinematicssupporting
confidence: 60%
“…Within this second scenario, there are no strict constraints on the relative ages between inner and outer bars. They may both be coeval, as in the case of the double-barred galaxy NGC 357 (de Lorenzo-Cáceres et al 2012). However, younger and more metal-rich inner bars, as those observed by de Lorenzo-Cáceres et al (2013) and mentioned before, are also in agreement, depending on the amount of gas present and the timescales for star formation.…”
Section: Introductionmentioning
confidence: 99%
“…Wozniak 2015). All observational studies performed so far on doublebarred galaxies agree that outer bars form prior to inner bars (de Lorenzo-Cáceres et al 2012, as confirmed by their stellar populations and star formation histories. Within this scenario, large-scale bars that have developed an inner bar should be already assembled systems growing accordingly in size and strength, while inner bars could still be immersed in the process of settling up.…”
Section: Assembly Of Outer and Inner Barssupporting
confidence: 59%